2004
DOI: 10.1890/03-0244
|View full text |Cite
|
Sign up to set email alerts
|

Horizons in Stream Biogeochemistry: Flowpaths to Progress

Abstract: Over the past 50 years, conceptual developments in stream ecology and ecosystem ecology have converged, thanks to biogeochemistry and the recognition that in situ processing on one hand and spatial translation of materials, processes, and influence along flowpaths on the other, unite to generate a holistic picture of ecosystem functioning at the landscape level. Early emphases in stream biogeochemistry involved organic carbon dynamics and whole-ecosystem budgets. These approaches were holistic but cumbersome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
154
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(157 citation statements)
references
References 71 publications
(56 reference statements)
2
154
0
1
Order By: Relevance
“…The chemistry of small streams integrates biogeochemical cycling in stream channels as well as the terrestrial systems they drain, and has played a key role in the development of ecosystem ecology (Fisher et al 2004). The small-watershed concept (Bormann and Likens 1967) advanced the study of terrestrial nutrient cycles with the idea that stream chemical loads represent nutrient losses from the wider ecosystem, and is today perhaps the most common example of forest biogeochemistry in introductory ecology textbooks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemistry of small streams integrates biogeochemical cycling in stream channels as well as the terrestrial systems they drain, and has played a key role in the development of ecosystem ecology (Fisher et al 2004). The small-watershed concept (Bormann and Likens 1967) advanced the study of terrestrial nutrient cycles with the idea that stream chemical loads represent nutrient losses from the wider ecosystem, and is today perhaps the most common example of forest biogeochemistry in introductory ecology textbooks.…”
Section: Introductionmentioning
confidence: 99%
“…3 holds and U ÂŒ R or U ÂŒ R ÂŒ 0 (e.g., during storm flows), then this must be true. Critically, however, high levels of nutrient accumulation and gaseous loss may occur along soil-to-stream flow paths (Mulholland 1992, Hedin et al 1998, Fisher et al 2004) and therefore stream losses may not equal losses from rooting zones of upland ecosystems but rather from ground-streamwater interfaces. Our results also point to conditions under which stream nutrient loads may not equal terrestrial losses: single-source nutrient inputs, low ground-water inflow, periods of high light and net biomass growth, and high rates of denitrification or burial.…”
mentioning
confidence: 99%
“…However, many situations with significance to riverine nutrient transport and processing at large temporal and spatial scales are outside the scope of the steady-state approach. These situations include conditions of fluctuating background flows and fluxes (Fisher et al 2004), high water residence time (e.g., long flowpaths and those containing wetlands, ponds, or large backwaters), and high discharge (e.g., large rivers, floods). Research in these biogeochemical frontiers would facilitate identifying the Quantifying phosphorus uptake using pulse and steady-state approaches in streams places and times at which nutrient removal mechanisms are meaningful to long-term dynamics, and would be valuable within the context of continuing global change.…”
Section: Introductionmentioning
confidence: 99%
“…Although the general approach has been cited as laborious (Fisher et al 2004), strengths relate to its methodological and mathematical elegance and simplicity. These characteristics have, fortuitously, facilitated widespread application of the model (Ensign and Doyle 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Peaks in seston concentration found in a deciduous European forest stream at midmorning and evening were attributed to diurnal rhythms in algal drift (Pozo et al 1994), but no diel patterns were found in either boreal (Naiman 1982) or glacier-fed alpine streams (Hieber et al 2003). Information about temporal patterns can help evaluate the sources of POC (Kendall et al 2001), quality of the energetic subsidy to downstream biota (RosiMarshall 2004), controls on transport (Pozo et al 1994), and lead to better estimates of baseflow POC fluxes, especially in streams with pulsed inputs of organic matter (Fisher et al 2004).…”
mentioning
confidence: 99%